Impact of Dietary Egg Yolk IgY Powder on Behavior, Meat Quality, Physiology, and Intestinal Escherichia coli Colonization of Broiler Chicks - Rehan, Ibrahim F.; Rehan, Ahmed F.; Abouelnaga, Ahmed F.; Hussein, Mohamed A.; El-Ghareeb, Waleed R.; Eleiwa, Nesreen Z.; Elnagar, Asmaa; Batiha, Gaber E.; Abdelgawad, Mohamed A.; Ghoneim, Mohammed M.; Hafiz, Amin A.; Gadallah, Hossam E.; et al. (Frontiers in Veterinary Science, 2022)
The current study investigated the impact of different concentrations of purified egg yolk immunoglobulin Y (IgY) supplemental food on growth performance, behaviors, cecal contents of Escherichia coli (E. coli), and meat quality of broiler chicks. Four dietary groups were given to 180 female Ross broiler chicks at random (n=45 for each). The control group was fed a standard diet only, whereas the other three experimental groups were fed the same basic diet supplemented with 1500 μg/mL, 3000 μg/mL, and 4000 μg/mL IgY respectively, for 42 days duration. A significant greater behavioral activities including, feeding, drinking, and dust bathing (P< 0.05) in the birds fed 4000 μg/mL of IgY compared to the control group. Greater weight gain of the crop, proventriculus, gizzard, and intestine (P< 0.05) are observed for broiler chicks fed 4000 μg/mL of IgY when compared by control group. After three weeks of feeding, the groups fed 3000 and 4000 μg/mL IgY had a significant lower E. coli count in muscle and cecal content (P< 0.05) when compared by control group. Moreover, dietary supplementation with 4000 μg/mL IgY at the third week and 3000 μg/mL IgY at the six week resulted in greater weight gain (P< 0.01) when compared by control group. Also, at week 3 chicks fed 4000 μg/mL of IgY had lower FCR (feed conversion ratio) when compared to the control group (P< 0.05). At week 6, chicks fed 3000 μg/mL of IgY had lower FCR than control (P< 0.05). The circulating Heterophiles/ Lymphocytes ratio was simply altered in birds fed variable IgY concentrations (1500 µg/mL, 3000 µg/mL, 4000 µg/mL) with no significance differences compared to the control group due to the individual resistance of each bird to the physiological stress. The addition of 4000 μg/mL IgY to the diet enhanced the nutritive value of meat, including protein, fat, and ash content (P< 0.05). Our study concluded that dietary supplementation of 3000 and/or 4000 μg/mL IgY improved the growth rates, behavioral activities, intestinal health indices, and meat quality of broiler chicks.